2007
DOI: 10.1128/iai.00635-07
|View full text |Cite
|
Sign up to set email alerts
|

Six Genes Are Preferentially Transcribed by the Circulating and Sequestered Forms of Plasmodium falciparum Parasites That Infect Pregnant Women

Abstract: In areas of stable malaria transmission, susceptibility to Plasmodium falciparum malaria increases during first pregnancy. Women become resistant to pregnancy malaria over successive pregnancies as they acquire antibodies against the parasite forms that sequester in the placenta, suggesting that a vaccine is feasible. Placental parasites are antigenically distinct and bind receptors, like chondroitin sulfate A (CSA), that are not commonly bound by other parasites. We used whole-genome-expression analysis to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 68 publications
6
69
0
Order By: Relevance
“…A scenario wherein novel proteins unrelated to PfEMP1 playing roles in the adhesive process cannot be ruled out. Consistent with these predictions, recent studies implicate novel proteins in IRBC adherence [13][14][15][16]. Thus, the development of a vaccine for placental malaria remains challenging.…”
mentioning
confidence: 67%
“…A scenario wherein novel proteins unrelated to PfEMP1 playing roles in the adhesive process cannot be ruled out. Consistent with these predictions, recent studies implicate novel proteins in IRBC adherence [13][14][15][16]. Thus, the development of a vaccine for placental malaria remains challenging.…”
mentioning
confidence: 67%
“…Two recent DNA microarray studies failed to identify parasite genes whose expression was related to disease severity (13,14). In contrast, microarray and proteomic studies of pregnancy malaria have identified sets of genes and proteins, including VAR2CSA, that are more abundant in parasites isolated from pregnant women than in those from children (15,16) or that are more abundant in placental parasites than in a laboratory-adapted reference strain (17).…”
Section: Introductionmentioning
confidence: 99%
“…We show that this technique excludes the majority of human globin and rRNA and enables the identification of parasite genes whose transcription levels vary among field isolates. In addition, NSR-seq detects most genes previously discovered by microarray analysis as upregulated in parasites infecting pregnant women, including the pregnancy malaria vaccine candidate var2csa (15), demonstrating that this technique is suitable for the identification of differentially regulated parasite genes. More importantly, NSR-seq identifies 4 genes that are expressed preferentially by children's parasites (glutamic acid-rich protein [garp/PFA0620c]; mature-parasite-infected erythrocyte surface antigen [MESA/PfEMP2/PFE0040c]; glycophorin-binding protein 2 [Gbph2/PF13_0010]; and probable protein PF10_0350]), which might have roles of particular importance in the pathogenesis of childhood malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Although these findings do not exclude the role of VAR2CSA in the binding of iE to CSA, they suggest that parasite binding to CSA might involve multiple binding ligands or a multiprotein complex comprising VAR2CSA PfEMP1 and other proteins, the identification of which remains an important goal. Microarray approach in transcriptome analysis of field isolates has found specific transcription of novel genes encoding potential surface antigens in fresh placental isolates (Francis et al, 2007;Tuikue Ndam et al, 2008). However, molecular, structural and functional data are still needed to the understanding the biological relevance of those PAM-specific antigens and thus aid in defining critical constructs as vaccine candidates.…”
Section: Challenges To Developing a Malaria Vaccinementioning
confidence: 99%